Texting 4 Sexual Health: Improving Attitudes, Intention, and Behavior Among American Indian and Alaska Native Youth. Issue 6 (November 2018) - Yao, Patricia; Fu, Rongwei; Craig Rushing, Stephanie; Stephens, David; Ash, Joan S.; Eden, Karen B.
Purpose . To design and test the effectiveness of a text messaging intervention to promote condom use and STI/HIV testing among American Indian and Alaska Native youth. Method . A total of 408 study participants, 15 to 24 years old, were recruited, consented, surveyed, were sent intervention messages, and were incentivized via text message over a 9-month period. Complete pre- and postsurvey data were collected from 192 participants using SMS short codes. A mixed-effects logistic regression model was used to analyze before–after change in responses assessing sexual health knowledge, attitude, self-efficacy, intention, and behavior. Results . Participants' condom use attitude, condom use behavior, and STI/HIV testing intention improved after the intervention ( p < .05). Frequent condom use increased from 30% to 42% and was retained by participants at least 3 months postintervention, and the intervention improved participants' intention to get tested for STI/HIV after changing sexual partners, increasing from 46% to 58% postintervention. Conclusions . Given the widespread use of cell phones by youth, text-based interventions may offer a feasible and effective tool to promote condom use and STI/HIV testing.